Multi-axial fatigue numerical crack propagation in cruciform specimens - Venanzio Giannella; Michele Perrella (Fracture and Structural Integrity)
Two cracks, initiated from the opposite tips of a central notch inclined by 45°, were considered in cruciform specimens made of Ti6246. A static load was applied to a cruciform arm while a cyclic load was applied along the other arm.